2017
DOI: 10.1097/md.0000000000005788
|View full text |Cite
|
Sign up to set email alerts
|

Micronodular pattern of organizing pneumonia

Abstract: Rationale:Organizing pneumonia (OP) is a clinicopathological entity characterized by granulation tissue plugs in the lumen of small airways, alveolar ducts, and alveoli. OP can be cryptogenic (primary) (COP) or secondary to various lung injuries.Patient concerns:We report the case of a 38-year-old male smoker with COP presenting in the form of diffuse micronodules on computed tomography (CT) scan and describe the clinical, radiological, and functional characteristics of micronodular pattern of organizing pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The current clinical treatment of COP is still based on corticosteroid therapy, and 65–80% of patients with COP achieve complete clinical and pathological remission after corticosteroid therapy. Although COP responds well to corticosteroids, it may be prone to relapse following treatment (23,24). COP may be induced by numerous factors, including viral infections and autoimmune diseases, but its pathogenesis remains incompletely understood and warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…The current clinical treatment of COP is still based on corticosteroid therapy, and 65–80% of patients with COP achieve complete clinical and pathological remission after corticosteroid therapy. Although COP responds well to corticosteroids, it may be prone to relapse following treatment (23,24). COP may be induced by numerous factors, including viral infections and autoimmune diseases, but its pathogenesis remains incompletely understood and warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…If these features are not detected, a surgical lung biopsy should be considered; however, small biopsy specimens are sufficient for diagnosis. In addition, the prevalence of a micronodular pattern of OP (MNOP) on radiological series is estimated to range from 10% to 24%; 4 however, the prevalence of a diffuse pattern in the total lung field of MNOP is rare. 4,5 CT pattern resembling HP has occasionally been observed in patients with immune checkpoint inhibitor (ICI)-induced pneumonia and described as centrilobular nodules, Copyright © 2020 by the American Thoracic Society bronchiolitis-like appearance, and tree-in-bud micronodularity; 6 however, the manifestation of diffuse pattern in the total lung fields of patients with ICI-induced pneumonia is rare.…”
Section: To the Editorsmentioning
confidence: 99%
“…If these features are not detected, a surgical lung biopsy should be considered; however, small biopsy specimens are sufficient for diagnosis. In addition, the prevalence of a micronodular pattern of OP on radiological series is estimated to range from 10% to 24% ( 4 ); however, the prevalence of a diffuse pattern in the total lung field of micronodular pattern of OP is rare ( 4 , 5 ).…”
mentioning
confidence: 99%
“…OP, cryptogenic or secondary, is a clinicopathological entity characterized by granulation tissue plugs in the lumen of small airways, alveolar ducts, and alveoli. An unusual radiological presentation corresponding to diffuse micronodular pattern mimicking miliary lung infiltration has been reported, and the prevalence of this micronodular pattern of OP (MNOP) in radiological series is estimated to range from 10% to 24% ( 2 , 3 ). The typical MNOP on CT imaging is widespread lung micronodules without diffuse ground-glass opacities, airspace consolidation, or cavitation.…”
mentioning
confidence: 99%
“…In large series of OP, the histological diagnosis was obtained on TBB specimens from 31% to 67% of cases. Importantly, most cases of MNOP were diagnosed by surgical lung biopsy ( 2 ). Regarding HP, the meta-analysis of 11 studies on TBB revealed a diagnostic yield of 64.3% ( 6 ).…”
mentioning
confidence: 99%